PELAKSANAAN PROMOSI DANAU WISATA SUNGAI SORIEK DI KABUPATEN KUANTAN SINGINGI - futri, Nur afyuni; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the implementation of the Soriek River Tourism Lake Promotion in Kuantan Singingi Regency. Personal Selling, Mass Selling, Sales Promotions, Public Relations and Direst Marketing. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are BUMDES, BUMDES Staff, Village Head, Village Staff and Visitors. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded that the Soriek River tourist attraction is conducting sales presentations and distributing brochures and giving discounts to visitors, holding competitions, giving prizes to visitors and collaborating with the government to carry out promotions. Keywords: Implementation. Promotion, Soriek River Lake